2015
DOI: 10.1016/j.brs.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-like Effects of Electroconvulsive Seizures Require Adult Neurogenesis in a Neuroendocrine Model of Depression

Abstract: Background Neurogenesis continues throughout life in the hippocampal dentate gyrus. Chronic treatment with monoaminergic antidepressant drugs stimulates hippocampal neurogenesis, and new neurons are required for some antidepressant-like behaviors. Electroconvulsive seizures (ECS), a laboratory model of electroconvulsive therapy (ECT), robustly stimulate hippocampal neurogenesis. Hypothesis ECS requires newborn neurons to improve behavioral deficits in a mouse neuroendocrine model of depression. Methods We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
66
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 26 publications
7
66
0
1
Order By: Relevance
“…Similar results have been demonstrated in rodent models of depression (Nakamura et al 2013; Schloesser et al 2015) and non-human primates (Perera et al 2007). …”
Section: Neuroplasticity Changes In Mdd and The Effects Of Antidepressupporting
confidence: 79%
“…Similar results have been demonstrated in rodent models of depression (Nakamura et al 2013; Schloesser et al 2015) and non-human primates (Perera et al 2007). …”
Section: Neuroplasticity Changes In Mdd and The Effects Of Antidepressupporting
confidence: 79%
“…It has been reported that seven ECS repetitions increased the number of DCX (+) cells containing tertiary dendrites (Schloesser et al . ). However, it remains unknown whether ECS enhances dendritic outgrowth in immature neurons.…”
Section: Discussionmentioning
confidence: 97%
“…While our present data were obtained from mice that did not show a depressive‐like phenotype, a recent report demonstrated that the antidepressant‐like effects of ECS require adult neurogenesis in a neuroendocrine model of depression (Schloesser et al . ). Identifying the molecular mechanisms that underlie each stage of neurogenesis could possibly lead to new targets for the development of antidepressant treatments.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The molecular mechanisms regulating adult neurogenesis during stress are complex and involve cross talk between inflammatory mediators, neurotrophic factors and cytokines (Egeland et al, 2015). An essential therapeutic role is suggested by experiments showing that antidepressantlike effects of electroconvulsive seizures require adult neurogenesis (Schloesser et al, 2015).…”
Section: Model Animals In Mood Disordersmentioning
confidence: 99%